The ginger bread man - Daly , Audrey (Ladybird Books Ltd.: London, 1993)
A charming Ladybird retelling of the classic Gingerbread Man tale$1 (Ba runaway gingerbread cookie meets various characters before being outsmarted by a clever fox.s